Pesantren and the Kitab Kuning: Pesantren Dynamics and Its Influence on the Kitab Kuning Traditions in Sukabumi - Yeni Ratna Yuningsih; Irfan Abubakar; Farhan Muzhaffar Rahman (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2023)
PurposeThis study aimed to better understand how the modernization of Islamic education has affected the patterns of learning Classical Literature (Kitab Kuning) in traditional pesantren in Sukabumi, West Java.MethodThis study used a qualitative method, by conducting in-depth interviews with 30 Kyais and pe-santren teachers in six pesantrens in Sukabumi. The six pesantrens represented old pesantren and were located in both the regency and city of Sukabumi.Results/findingsIn general, the modernization of Islamic education in pesantren in Sukabumi has not had much impact on the ways of learning Kitab Kuning which still apply classical methods. Exceptions oc-cur in a small number of pesantren which still all adhere to a pure Salafiyah system, such as Pe-santren An-Nidzom, Selabintana, and Pesantren Assalafiyah, Babakan, Tipar.ConclusionDespite minimal modernization of their education system, pure Salafiyah pesantrens have tried to apply limited modernization to the pattern of teaching of Kitab Kuning. Two new models have been adapted: First, the application of the Amtsilati method, a fast way of learning the Kitab Kuning discovered in 2002. Second, the application of an intensive learning strategy by placing selected students in intensive classes. Further studies need to be carried out to explore the effec-tiveness of the new method of learning Kitab Kuning in comparation to the classical one.